Loss of Neurofascin-186 Disrupts Alignment of AnkyrinG Relative to Its Binding Partners in the Axon Initial Segment - Alpizar, Scott A.; Baker, Arielle L.; Gulledge, Allan T.; Hoppa, Michael B. (Frontiers in Cellular Neuroscience, 2019)
The axon initial segment (AIS) is a specialized region within the proximal portion of the axon that initiates action potentials thanks in large part to an enrichment of sodium channels. The scaffolding protein ankyrinG is essential for the recruitment of sodium channels as well as several other intracellular and extracellular proteins to the AIS. In the present study, we explore the role of the cell adhesion molecule neurofascin-186 (NF) in arranging the individual molecular components of the AIS in cultured rat hippocampal neurons. Using a CRISPR depletion strategy to ablate NF expression we found that the loss of NF selectively perturbed ankyrinG accumulation and its relative proximal distribution within the AIS. We found that the overexpression of sodium channels could restore ankyrinG accumulation, but not its altered distribution within the AIS without NF present. We go on to show that although the loss of NF altered ankyrinG distribution, sodium channel function within the AIS remains normal. Taken together, these results demonstrate that the regulation of ankyrinG and sodium channel accumulation within the AIS can occur independently of one another, potentially mediated by other binding partners such as NF.